QARAQALPAQ ÁDEBIYATÍNDA TÁRIYIP JANRÍ - Sh.Djangabaeva, H. (SCIENCE and SOCIETY, 2024)
The Karakalpak literature mentions the origins of the tariyp (description) genre, the period of formation, similarities and differences with the ode and kasida genres.